Correlation And Regression Analysis For Researching Sustainable Development Of A Diversified Company - Azieva, Raisa H. (Opción, 2019)
The research objective is to develop an approach to production diversification for oil companies under unstable global economy, changeful supply and de- mand for energy sources, and high oil prices. The study method is correlation and regression analysis that allows identifying the impact of certain factors on performance. The paper proposes an algorithm of such analysis that provides awareness, assessment, and risk reduction. Given that renewable power gen- eration is seeing fast growth, diversification has become a promising direction for oil companies’ development. It allows balancing risk and economic effi- ciency, assessing risks and making a forecast of future financial flows.